Clinicopathological Study of Ovarian Masses in Adolescent Girls and Young Women in a Tertiary Care Hospital - Kundu, Soumya; Bhattacharyya, Aditi; Nandy, Sumit; Nayak, Pamela; Bala, Arpita (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Ovarian masses include both neoplastic and non-neoplastic lesions. Fortunately, though most ovarian masses in adolescents are benign, about 10% turn out to be malignant. Thus, ovarian tumours constitute an important part of paediatric oncology and often create diagnostic dilemmas. The present study aimed to calculate the frequency and clinicopathological patterns of ovarian masses in adolescent and young females and briefly discuss and compare with the existing literature. Methods This was a retrospective study conducted at the Department of Pathology of a tertiary care hospital in West Bengal, India. All tissue samples of ovarian masses received in the Pathology department between 10 to 20 years of age group over 6 years (January 2016-December 2021) were included in this study. We evaluated the clinicopathological parameters of the cases. The statistical analysis was performed using Epi Info 7 software. Results A total of 53 cases were included in present study of the defined age group over 6 years (January 2016 – December 2021), of which 2 had bilateral lesions, so a total of 55 ovarian masses were studied. Of 55 ovarian masses, 50 (90.9%) were benign tumours or non-neoplastic lesions and 5 ovarian masses (9.1%) were malignant. Mature cystic teratoma was the most common type of tumour in this age group. Conclusions Ovarian masses in perimenarchal and young adults show diversity in the histological spectrum. Although most are benign, early diagnosis preserves fertility in this tender age group.